Les connaissances de lecture au service des compétences scripturales : cas de 1ère année moyenne - Didi Fatma; Abbou Yousra (University of Eloued جامعة الوادي, 2025)
Our research, entitled "Reading Knowledge in the Service of Writing Skills: The Case of First-Year Middle School Students", falls within the framework of FLE (French as a Foreign Language) didactics and addresses learners’ weaknesses in written production. It responds to the following research question: How do the knowledge acquired during reading sessions improve the written production of first-year middle school students? The main objective of this work is therefore to demonstrate to what extent reading affects learners' writing ability, enabling them to reuse previously acquired knowledge in their own written texts. To achieve this goal, we conducted a comparative study by analyzing learners' written productions before and after reading sessions using model texts. This experiment allowed us to prove the impact of reading on writing skills and confirm our initial hypotheses through the results obtained. In short, applying knowledge gained from reading sessions significantly improves learners' writing skills. تندرج دراستنا المعنونةبـ "المعارف القرائية في خدمة المهارات الكتابية: حالة تلاميذ السنة الأولى متوسط" ضمن إطار تعليمية اللغة الفرنسية كلغة أجنبية، وهي تعالج ضعف المتعلمين في الإنتاج الكتابي. فيُجيب عن الإشكالية التالية: كيف تساهم المعارف المكتسبة خلال حصص القراءة في تحسين الإنتاج الكتابي لدى تلاميذ السنة الأولى متوسط؟ الهدف الرئيسي من هذا العمل هو إبراز مدى تأثير القراءة على الكتابة، حتى يتمكن من إعادة توظيف المعارف المكتسبة في كتاباته الخاصة. ولتحقيق هذا الهدف، قمنا خلال تحليل إنتاج التلاميذ الكتابية قبل وبعد حصص قراءة نصوص نموذجية. وقد سمح لنا هذا التحليل بالوقوف على المهارات الكتابية، وتأكيد الفرضيات التي انطلقنا منها، من خلال النتائج المتوصل إليها باختصار أن توظيف المعارف المستخلصة من حصص القراءة يحسّن بشكل ملحوظ من الكفاءات الكتابية لدى المتعلمين
Master. Didactique et Langues appliquée. 2025
Keywords: FLE didactics – Reading – Written production – Writing skills – Integrated learning; تعليمية اللغة الفرنسية – القراءة – الإنتاج الكتابي – الكفاءات الكتابية – التعلم المدمج